1985
DOI: 10.1007/bf00544351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various hypoglycaemic sulphonylureas on the cardiotoxicity of glycosides

Abstract: In diabetic patients it has been shown that tolbutamide and carbutamide enhanced and glibenclamide did not influence the incidence of digitalis intoxication, or that of multifocal ectopic beats or coupling due to premature ectopic ventricular beats during digitalis therapy. In rabbits glibenclamide decreased and tolbutamide and carbutamide increased strophanthidin toxicity in a dose dependent manner. It was concluded that glibenclamide should be preferred to tolbutamide or carbutamide in digitalis-treated diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This drug can attenuate the ischemically induced changes in the ST-segment in intact anesthetized or unanesthetized animals [Kondo et al, 1996;Billman et al, 1998]. Glibenclamide also prevented arrhythmias induced by ischemia in isolated hearts [Pogatsa et al, 1988;Wolleben et al, 1989;Kantor et al, 1990;Gwilt et al, 1992;Tosaki et al, 1995]. Furthermore, both glibenclamide and glimepride reduced blood glucose and decreased the incidence of irreversible ventricular fibrillation induced by reperfusion (after a 6-minute coronary occlusion) in anesthetized rats [El Reyani et al, 1999].…”
Section: Atp-sensitive Potassium Channel Antagonists: Ischemia-selectmentioning
confidence: 99%
“…This drug can attenuate the ischemically induced changes in the ST-segment in intact anesthetized or unanesthetized animals [Kondo et al, 1996;Billman et al, 1998]. Glibenclamide also prevented arrhythmias induced by ischemia in isolated hearts [Pogatsa et al, 1988;Wolleben et al, 1989;Kantor et al, 1990;Gwilt et al, 1992;Tosaki et al, 1995]. Furthermore, both glibenclamide and glimepride reduced blood glucose and decreased the incidence of irreversible ventricular fibrillation induced by reperfusion (after a 6-minute coronary occlusion) in anesthetized rats [El Reyani et al, 1999].…”
Section: Atp-sensitive Potassium Channel Antagonists: Ischemia-selectmentioning
confidence: 99%
“…It has been reported, in rabbits and rats, that glibenclamide decreased, but tolbutamide and carbutamide increased strophanthidin toxicity (Pogatsa, Koltai, Balkanyi, Devai & Kiss, 1985; Pogatsa et al. , 1988).…”
Section: Katp Channels and Potassium Currentsmentioning
confidence: 99%
“…Concomitantly administered diuretic agents may increase the incidence of digitalis toxicity both by decreasing the glomerular filtration rate caused by volume depletion and by inducing a variety of electrolyte disturbances, including hypokalaemia, hypomagnesaemia, and (for thiazide diuretics) hypercalcaemia (Hauptman & Kelly, 1999;Ma, Brady, Pollack & Chan, 2001). It has been reported that in digitalized non‐insulin‐dependent diabetics, multifocal ectopic ventricular beats could be observed in none among the 80 glibenclamide‐treated diabetics (Pogatsa et al. , 1988).…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In addition, drug interactions can cause profound hypoglycemia (Table 2). [23][24][25][26][27][28][29][30][31][32][33] Factors that increase the risk of having a hypoglycemic episode include advanced age, poor nutrition, alcohol consumption, renal and hepatic disease, and polypharmacy. 2,34 Clinically, time to peak and duration of action are the most important considerations when anticipating hypoglycemia after sulfonylurea overdose (Table 1).…”
Section: S U L F O N Y L U R E a Smentioning
confidence: 99%